Modalities in venous thromboembolism prophylaxis and symptomatic venous thromboembolism occurrence in critically ill surgical patients (THAI-SICU study) - Akaraborworn O. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: This report aimed to demonstrate the current modality of venous thrombomebolism (VTE) prophylaxis at the University-based critical, surgical care units (SICUs) and the occurrence of VTE during SICUs admission. Material and Method: The data were analyzed from a multicenter prospective observational study that was conducted in 9 university based SICUs in Thailand (THAI-SICU study). VTE prophylaxis and occurrence were recorded daily and VTE events which included deep vein thrombosis (DVT) and pulmonary embolism (PE) were collected only after symptomatic events occurred and confirmed the diagnosis by Doppler ultrasonographic examination or other imaging modalities. Results: A total of 385 in 4,652 cases (8.3%) received VTE prophylaxis. The modalities of VTE prophylaxis were significant difference depended on the admission diagnosis, patient age, and severity of diseases. The result of total VTE occurrence was 18 patients (0.4%) and mortality was 4 in 18 patients (22.2%). Of these, DVT occurred in 14 patients (0.3%) and mortality was 3 of 14 patients (21.4%), and the PE occurred in 4 patients (0.1%) and mortality was 1 of 4 patients (25.0%). Conclusion: The VTE prophylaxis rate was low in Thai University based SICUs. Although the overall incidence of symptomatic VTE in the SICUs low, the mortality rate was high in this cohort.